Corticosteroid choice and clinical outcomes for asthma exacerbations in the primary care setting. (1st February 2022) - Navanandan, Nidhya; Moss, Angela; Tanverdi, Melisa; Ambroggio, Lilliam; Brittan, Mark
Abstract: Objective: To evaluate clinical outcomes in young children with acute asthma exacerbations treated with prednisone/prednisolone versus dexamethasone in the primary care setting. Methods: Retrospective cohort study of children ages 3-9 years with a primary care clinic visit for asthma and an associated oral corticosteroid (OCS) prescription fill in the Colorado All Payers Claim Database between 2/2013-3/2019. This was a secondary analysis of a dataset extracted to analyze risk of future development of asthma in younger children. The primary outcome was subsequent ED visit or hospital admission for asthma within 2-14 days after the index clinic visit. Demographics and asthma health services characteristics were assessed. Multivariable logistic regression was used to estimate the association between type of OCS prescription filled within 1 day of the index clinic visit and the primary outcome. Results: There were 3236 index clinic visits for asthma for 1918 children during the study period. Sixty-two percent were male and 66% were 3-4 years old. Prednisone/prednisolone accounted for 84% of OCS prescriptions fills within 1 day of the index clinic visit. One percent visited the ED and 1% required hospital admission within 2-14 days. In multivariate analysis, there was no statistical association between type of OCS prescribed and the primary outcome (OR 0.82; 95% CI: 0.37-1.8). Conclusions: There are no differences in clinical outcomes by type of OCS prescribed for acute asthma exacerbations in the primary care setting. Due to better adherence and side effect profile, primary care providers may consider to use dexamethasone as the preferred OCS.